ERCP–PTBD Rendezvous Method in a Patient with Pancreatic Head Carcinoma and Duodenal Infiltration: A Case Report - Nikko Darnindro; Rabbinu Rangga Pribadi; Edi Mulyana (The Indonesian Society for Digestive Endoscopy, 2026)
Advanced pancreatic head cancer with tumor infiltration into the duodenum is capable of distorting the anatomy and is extremely challenging for selective biliary cannulation during ERCP. In these situations, the ERCP–PTBD rendezvous method served as a valuable alternative. Therefore, this case report aimed to describe the case of a 75-year-old man who presented with obstructive jaundice. On examination, the patient was tachycardic and febrile (38.0°C), with pale conjunctivae and marked scleral icterus. A palpable mass was observed in the epigastric region, and laboratory evaluation showed a total bilirubin level of 18.64 mg/dL. Furthermore, MRCP showed a mass in the pancreatic head infiltrating the duodenum, leading to significant intra- and extrahepatic biliary dilatation. The patient was initially subjected to transhepatic biliary drainage (PTBD), followed by an ERCP using the rendezvous method due to the tumor-related distortion of the papilla. During this procedure, a guidewire was advanced through the PTBD tract and navigated under fluoroscopy into the duodenum, facilitating biliary access and successful placement of a biliary stent. Two days after the intervention, the condition improved, with bilirubin decreasing to 8.91 mg/dL, and the patient was subsequently discharged in stable condition. This case showed the rendezvous method as an effective alternative biliary drainage strategy for patients in whom conventional ERCP was hindered by tumor-related anatomical alterations.